2002
DOI: 10.1016/s0002-9440(10)61123-6
|View full text |Cite
|
Sign up to set email alerts
|

Carp, a Cardiac Ankyrin-Repeated Protein, and Its New Homologue, Arpp, Are Differentially Expressed in Heart, Skeletal Muscle, and Rhabdomyosarcomas

Abstract: Arpp, a protein containing an ankyrin repeat domain, PEST sequence, and proline-rich region, is a novel ankyrin-repeated protein highly homologous to Carp, which is proposed to be the putative genetic marker for cardiac hypertrophy. In this study, we comparatively analyzed expression of Arpp and Carp protein in skeletal and cardiac muscles and rhabdomyosarcomas (RMSs). In adult skeletal muscle, Arpp was preferentially expressed in the nucleus and cytoplasm of type I fibers, whereas Carp was barely detectable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
84
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 13 publications
(16 reference statements)
12
84
3
Order By: Relevance
“…Consistent with our previous data obtained using rabbit polyclonal Ab, 3,5 ARPP was found to be highly expressed in skeletal muscle (data not shown). In addition, we found unexpectedly that ARPP was expressed in part of the renal tubule (Figure 2a).…”
Section: Selective Expression Of Arpp In Part Of the Distal Renal Tubulesupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with our previous data obtained using rabbit polyclonal Ab, 3,5 ARPP was found to be highly expressed in skeletal muscle (data not shown). In addition, we found unexpectedly that ARPP was expressed in part of the renal tubule (Figure 2a).…”
Section: Selective Expression Of Arpp In Part Of the Distal Renal Tubulesupporting
confidence: 93%
“…1 Unexpectedly, ARPP was found to be expressed at a high level in almost all rhabdomyosarcomas. 3,4 On the other hand, in normal tissues, we found that ARPP was preferentially expressed in skeletal and cardiac muscle. 1,3 Moreover, ARPP was abandunt in mouse denervated gastrocnemius muscles, 5 whereas the biological function of ARPP is largely unknown.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Coexpression of CARP and YB-1 has been shown to repress the transcriptional target of YB-1, MLC-2v, which is required for the maintenance of cardiac contractility and ventricular chamber morphogenesis (Nguyen-Tran et al, 1999). However, our group and another group recently reported that CARP was localized mainly in the cytoplasm as well as in the nucleus of fetal and adult heart (Bang et al, 2001;Ishiguro et al, 2002). Furthermore, we showed in this study that CARP is localized in the sarcomeric I-Z-I areas of regenerating skeletal muscle.…”
Section: Discussionmentioning
confidence: 75%